Effect of renal function on the risk of thrombocytopaenia in patients receiving linezolid therapy: A systematic review and meta‐analysis. Issue 2 (10th October 2021) - Shi, Changcheng; Xia, Junbo; Ye, Jian; Xie, Yaping; Jin, Weizhong; Zhang, Wei; Wang, Liusheng; Ding, Xuping; Lin, Nengming; Wang, Limin
Abstract : Aims: The association of renal function and linezolid‐induced thrombocytopaenia (LIT) remains controversial. We performed a meta‐analysis to determine whether impaired renal function is associated with an increased LIT risk. Methods: We conducted a systematic search of PubMed, EMBASE and the Cochrane Library from inception to February 2021 for eligible studies evaluating the relationship between renal function and LIT. Indicators of renal function included renal impairment (RI), severe RI, haemodialysis status, creatinine clearance rate (Ccr) and estimated glomerular filtration rate (eGFR). Unadjusted and adjusted estimates and 95% confidence intervals (CIs) were calculated separately using a random‐effect model. Results: A total of 24 studies with 3580 patients were included in the meta‐analysis. RI patients had an increased LIT risk compared to non‐RI patients in both the unadjusted (OR 3.54; 95% CI 2.27, 5.54; I 2 = 77.7%) and adjusted analyses (OR 2.51; 95% CI 1.82, 3.45; I 2 = 17.9%). This association persisted in the subset of studies involving only patients receiving a fixed conventional dose (600 mg every 12 h) and other subgroup analyses by ethnicity, sample size and study quality. Moreover, the LIT risk was significantly higher in patients with severe RI and haemodialysis than in patients without severe RI and haemodialysis. The eGFR and Ccr were significantly lower in LIT patients than in non‐LIT patients. Conclusions: Impaired renal function is associated with an increased risk of LIT. A reduced linezolid dose may be considered in RI patients at a low risk of treatment failure, ideally guided by therapeutic drug monitoring.